Desain Kelembagaan dan Kepemimpinan Fasilitatif dalam Collaborative Governance : Studi Pada Pengembangan Desa Wisata Detusoko Barat - Bidi, Ermenilda Sedo; Mahyuni, Luh Putu (Riviera Publishing, 2025)
Tourism village development cannot operate independently without support and collaboration among government actors, the community, and other stakeholders trough collaborattive governance. However, this process often encounters obstacles, particularly in establishing effective institutional structures and leadership capable of directing and accomodating diserve interests. This study aims to analyze the institutional design and the role of facilitative leadership in the collaboration of tourism village development in Detusoko Barat. This research employs a descriptive qualitative approach with data collected trough in-depth interviews, and documentation. The findings show that the institusional design has been shaped trough the involvement of village government, tourism awareness groups (Pokdarwis), local communities, and external partners. Nevertheless, challengers remain in terms of formal regulations and transparency mechanisms. On the other hand, facilitative leadership exercised by the Village Head and community leader play a vital role in building trust, encouraging participation, and bridging differences among actors. These findings affirm that success of collaborative tourism village development is strongly influenced by inclusive institutional design and adaptive, communicative facilitative leadership.